2015
DOI: 10.1055/s-0035-1547539
|View full text |Cite
|
Sign up to set email alerts
|

Brain Death: The Asian Perspective

Abstract: Asia is the largest and most populous continent in the world with people from many diverse ethnic groups, religions and government systems. The authors surveyed 14 countries accounting for the majority of Asia's population and found that, although the concept of brain death is widely accepted, there is wide variability in the criteria for certification. Although most Asian countries have adopted the "whole-brain" concept of brain death, most countries with past colonial links to the United Kingdom follow the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…There is no uniform neurological standard in death determination because of the variability in practices and perceptions of the global medical community about brain death (Wahlster et al 2015 ). The neurological determination of death varies among countries with regard to the use of whole brain criteria or brainstem criteria, and the mandatory performance of confirmatory tests (Ding et al 2015 ; Citerio and Murphy 2015 ; Chua et al 2015 ; Varelas 2016 ; Cameron et al 2016 ). Confirmatory tests include neuroimaging of cerebral blood flow and electrophysiological studies of the cerebral hemispheres and the brainstem.…”
Section: Introductionmentioning
confidence: 99%
“…There is no uniform neurological standard in death determination because of the variability in practices and perceptions of the global medical community about brain death (Wahlster et al 2015 ). The neurological determination of death varies among countries with regard to the use of whole brain criteria or brainstem criteria, and the mandatory performance of confirmatory tests (Ding et al 2015 ; Citerio and Murphy 2015 ; Chua et al 2015 ; Varelas 2016 ; Cameron et al 2016 ). Confirmatory tests include neuroimaging of cerebral blood flow and electrophysiological studies of the cerebral hemispheres and the brainstem.…”
Section: Introductionmentioning
confidence: 99%
“…1 2 3 4 5 6 However, some countries still do not have medical standards for BD/DNC, and there is also international and intranational variability between the protocols that do exist. 3 4 7 8 9 …”
Section: Introductionmentioning
confidence: 99%
“… 12 Despite this, the review of worldwide BD/DNC protocols reported by Wijdicks in 2002 included only 22 countries in Asia and the Pacific (39% of the countries in this region), 18 of which had protocols for BD/DNC (83% of countries reviewed in the region, 35% of countries in Asia and the Pacific). 4 Similarly, the international survey performed by Wahlster et al 3 in 2015 of physicians who are involved in declarations of BD/DNC included only 27 countries in Asia and the Pacific (47% of countries in the region), 17 of which had protocols for BD/DNC (63% of countries reviewed in the region, 30% of countries in the region), while the review by Chua et al 9 in 2015 of Asian protocols included protocols from only 14 countries (25% of countries in Asia and the Pacific).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations